DEVELOPMENT OF CLOUD-BASED MEDIA PLAYER USING MICROSOFT AZURE SERVICES - Chong, Fong Kim; Deshinta, Arrova Dewi (INTI International University, 2018)
Playing songs offline consumes internal storage capacity of a device. Besides, playing songs, most of the time is an individual acting as a hobby and many song listeners do not have a common platform to share their hobby with others. By putting it on the cloud, the internal storage capacity can be reduced and the chance to share the common hobby with others is available. This paper aims to present the development of a Cloud-Based Media Player (CBMP) to ease the users in managing their song files and sharing with others. The CBMP utilizes a website as the main controller and connects to the Microsoft Azure Services to host the music database. Two separate sections are created for the user to upload and download their songs as private and share sections. Accordingly, users can choose the favored section they want to access. Not only features to upload and download songs are provided, but the CMBP also provides a search function that enables users to search songs in both different to make a search process faster. Due to latency in the cloud services, the suggested song format for CMBP is.MP3 files. The .MP3 files promote better compression rate than .MP4. Besides, .MP4 has higher latency that makes users waiting longer for processing the songs. The .MP3 is a light load and makes buffering time faster to process user’s favorite songs. The CBMP is developed using Visual Studio 2017, SQL Server Management Studio and Microsoft Azure Portal with the database connection.